Erectile Dysfunction Patients In Institut Urologi & Nefrologi (Iun), Hospital Kuala Lumpur (Hkl) And Clinical Trial With Transuretheral Alprostadil (Muse®) - Nasuha , Noor Azam (2001)
The aim of this study was to evaluate the factors contributing towards erectile dysfunction (ED) in patients followed-up in the Institut Urologi & Nefrologi, Hospital Kuala Lumpur between 1st . March 1999 to 31st . August 1999. One hundred and fiftyfour patients were included in this study. The mean age of the patients was 52.68 years. The youngest was 22 and the oldest was 76 year-old. Most were between the age of 45 and 65 year-old. Diabetes mellitus and hypertension played a major role as contributing factors in the overall study population. 45.4% of the patients have diabetes mellitus and 29.2% have hypertension. 41.5% of the patients have single contributing factor towards erectile dysfunction whereas 29.2% have two and 10.4% of the patients have three contributing factors. In 18.2% of the studied patients the cause of ED were unknown. In term of racial distribution, Malays contributed 48.7% of the study sample; Indian 25.3% and Chinese constitute about 22.1 %. 35 patients who fulfilled the inclusion criteria were enrolled in the clinical trial with transurethral alprostadil (MUSE®). Thirty patients (85.6%) completed the in-clinic titration phase. Of these, 18 patients (60%) responded well to the MUSE® and they were sent home with the medication. However only 33.3% of patients completed the home phase. In conclusion, diabetes mellitus plays an important role in our patients with erectile dysfunction and MUSE® is one of the alternative treatment for such condition.